Optimized Reproduction, Collection, Transmission, Processing, and Display of Measurement Data Obtained Using the National Standard of Voltage Unit – Volt - Popko, V. V.; Sentemova, D. V.; Yarmalovich, M. A. (Measurement techniques, 2021)
Issues associated with automating the calibration of standard DC voltage measuring instruments are considered. An automatic calibration system is developed, studied, and implemented. This system comprises a hardware and software system containing measuring instruments from the National Standard of Voltage Unit – Volt and additional modules. The automatic system is created on the basis of the Python programming language using metrological principles. The studied calibration results of DC voltage standards, i.e., the obtained calibration results (assigned actual value with expanded uncertainty) are analyzed in automatic and manual modes, as well as using the 10 V Josephson voltage standard known as supraVOLTcontrol. As well as significantly reducing labor costs, the application of this automatic system to study the integral instability (nonlinearity) of a digital voltmeter allows measurement duration to be reduced, as well as providing flexibility and reconfiguration capability depending on issues that emerge during research.